ENHANCEMENT OF TRIACYLGLYCEROL IN CHLORELLA PYRENOIDOSA BY UV IRRADIATION - BINDIYA PANDEY; SOWMYA RAYA; KINNERA KALLAM; CHANUKYA REDDY BOMMAREDDY; SUJANA KOKKILIGADDA; MAHESWARA REDDY MALLU (International Journal of Pharma and Bio Sciences, 2016)
Microalgae with rich oil content are the promising alternatives for the depleting fossil fuel reserves, but there needs a great deal of work to be done in improving the lipid content of the microalgae strains. In this study, strain improvement in Chlorella pyrenoidosa was carried out for enhancing the production of neutral lipids mainly constituting triacylglycerol (TAG) which is the major source of biodiesel using UV radiation. The microalgal culture was exposed to different UV irradiation for different time periods and the results showed an increase in both biomass and TAG yields. A highest increase of 2.22 fold in biomass and 2.5 fold in TAG over control was observed for UV irradiation of 25 mins and 20 mins respectively. Gas chromatographic analysis of neutral lipid fractions from total lipids of UV irradiated samples showed an increase in percentage of some of the monounsaturated fatty acids which is considered as one of the preferred property of the biodiesel1.